On minimal ideal triangulations of cusped hyperbolic 3‐manifolds. Issue 1 (22nd November 2019) - Jaco, William; Rubinstein, Hyam; Spreer, Jonathan; Tillmann, Stephan
Abstract: Previous work of the authors studies minimal triangulations of closed 3‐manifolds using a characterisation of low degree edges, embedded layered solid torus subcomplexes and 1‐dimensional Z 2 ‐cohomology. The underlying blueprint is now used in the study of minimal ideal triangulations. As an application, it is shown that the monodromy ideal triangulations of the hyperbolic once‐punctured torus bundles are minimal.